The Influence of Service Quality, Brand Image, Trust, Security and Technology on Customer Satisfaction of Movin By Mandiri Taspen Users - Naufal Haidar Farras; Erric Wijaya (LPPPIPublishing, 2026)
This study aims to examine the influence of service quality, brand image, trust, security, and technology on customer satisfaction among users of the Movin by Mandiri Taspen mobile banking application, with a case study at Bank Mandiri Taspen KCP Batu. A quantitative approach was applied using a survey of 93 respondents selected through purposive sampling. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the SmartPLS software. The findings reveal that security and technology have a positive and significant effect on customer satisfaction. In contrast, service quality, brand image, and trust do not show a statistically significant influence. These results indicate that for the retirement customer segment, system security and technological performance are more influential in shaping satisfaction compared to relational and reputational factors. This study contributes to the literature on digital banking services by emphasizing the importance of strengthening security systems and improving technological features to enhance customer satisfaction, particularly within the retirement segment.